CYLD Cutaneous Syndrome: Familial Cylindromatosis, Brooke-Spiegler Syndrome and Multiple Familial Trichoepitherioma - Kurimoto, Takahiro; Oiso, Naoki; Miyake, Muneharu; Kawada, Akira (IntechOpen, 2013)
None